FORMULASI VIRGIN COCONUT OIL(VCO) DAN PENGEMULSI LESITIN KEDELAI TERHADAP STABILITAS EMULSI DAN SIFAT ORGANOLEPTIK PASTA KACANG MERAH [Formulation of Virgin Coconut Oil (VCO)and emulsifier lechitin of soy on the emultion stability and sensory characteristic of red beans paste - Susilawati Susilawati; Ribut Sugiharto; Suci Marita Damaiyanti (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2016)
Red beans and VCO are produced abundantly in Indonesia, but are not fully utilized. In this research, red beans and VCO were processed into red beans paste product as food diversification efforts. The objective of this research was to obtain the best formulationof VCO and lechitin addition to produce the best emultion stability and sensory characteristic the red beans paste. The experiment was arranged in a Complete Randomized Block Design (CRBD) with one factor and four repetitions. The treatments had 6 levels comparison of VCO and lechitin (K), that were K1 (30%:0,25%), K2 (45%:0,25%), K3 (60%:0,25%), K4 (30%:0,5%), K4 (45%:0,5%), K6 (60%:0,5%). The data were analyzed using Barlett test to find homogenity, furthermore the Tuckey test was used to test the additivity, then analyzed using ANOVA to test the effect of the treatments further analyzed with Least Significant Difference (LCD) test at 5% and 1% level. The results showed that K4 are the best formulation to produce red beans paste with the score of texture was 3,45 (somewhat like), the score of color was 3,68 (like), the score offlavor was 3,65 (like),the score of taste was 3,78 (like), the score ofspreadability was 3,38 (like), the emulsion stability was 0,247%. The proximate analyzed of K4 resulted that the moisture, fat, carbohydrate, protein, ashes, and crude fiber contents were 30,01%, 11,57%, 50,45%,6,48%, 1,49 %, and 8,97%.Keywords: emultion stability, red bean pastes, VCO.